GE_GERICHTE P/12985/2019 vom 26. Juni 2023 - GE Cour de justice (2023)
IN DUBIO PRO REO;LÉSION CORPORELLE SIMPLE;CONTRAINTE(DROIT PÉNAL);PRINCIPE DE L'ACCUSATION;PLAINTE PÉNALE;RETRAIT(VOIE DE DROIT) | CP.123.al1; CP.181; CP.30.al1; CPP.304.al1; CP.33.al2; CPP.325.al1